2008
DOI: 10.1002/prot.21883
|View full text |Cite
|
Sign up to set email alerts
|

A phospho‐sugar binding domain homologous to NagB enzymes regulates the activity of the central glycolytic genes repressor

Abstract: CggR belongs to the SorC family of bacterial transcriptional regulators which control the expression of genes and operons involved in carbohydrate catabolism. CggR was first identified in Bacillus subtilis where it represses the gapA operon encoding the five enzymes that catalyze the central part of glycolysis. Here we present a structure/function study demonstrating that the C-terminal region of CggR regulates the DNA binding activity of this repressor in response to binding of a phosphorylated sugar. Molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…These observations are in good agreement with our previous studies on CggR/DNA interactions by fluorescence anisotropy which showed that none of these phospho-sugars can prevent the cooperative binding of CggR to its target DNA as FBP does (18). It is also noteworthy that the marginal peaks detected in the mass range corresponding to the 2:1 CggR/ O R complex are slightly more intense in the case of F6P than of GBP, which is also in good agreement with our previous findings indicating that F6P at high concentration (>5 mM) can indeed alter CggR/DNA-binding cooperativity (18). Unfortunately, the effect of the different sugars at high concentrations could not be tested here because of severe reduction in the signal-to-noise ratio of the mass spectra.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These observations are in good agreement with our previous studies on CggR/DNA interactions by fluorescence anisotropy which showed that none of these phospho-sugars can prevent the cooperative binding of CggR to its target DNA as FBP does (18). It is also noteworthy that the marginal peaks detected in the mass range corresponding to the 2:1 CggR/ O R complex are slightly more intense in the case of F6P than of GBP, which is also in good agreement with our previous findings indicating that F6P at high concentration (>5 mM) can indeed alter CggR/DNA-binding cooperativity (18). Unfortunately, the effect of the different sugars at high concentrations could not be tested here because of severe reduction in the signal-to-noise ratio of the mass spectra.…”
Section: Resultssupporting
confidence: 93%
“…CggR is a member of the SorC family of bacterial transcriptional repressors, characterized by an N-terminal DNA-binding domain (DBD) followed by a phospho-sugar binding (PSB) domain homologous to glucosamine-6-phosphate deaminases from the NagB family (18). Other characterized members of this family are the sorbitol operon regulator SorC from Klebesiella pneumoniae (19) and the deoxyribonucleoside repressor DeoR from B. subtilis (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the binding activity and specificity of the CggR protein, the central glycolytic gene repressor, have been studied in detail. 4,5 Together with the DeoR protein of B. subtilis, these are the only members of the SorC family that have been purified and characterized in vitro. 6,7 K. pneumoniae SorC is the single transcriptional repressor of the sor operon, 8 which clusters seven genes (sorCDFBAME) that encode proteins involved in L-sorbose uptake and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…A sequence analysis of CggR revealed a winged helix domain at the N-terminus, as found for example in transcription factors like SorC and DeoR [85]. On the contrary, the Cterminal domain, which comprises residues 100-343, showed similarities with glucose-6-phosphate deaminases, including NagB.…”
Section: Cggr -A Mediator Of Ccpa-independent Catabolite Regulationmentioning
confidence: 94%